Fator de crescimento do endotélio vascular na viabilidade do retalho musculofasciocutâneo transverso do reto do abdome, em ratos submetidos à nicotina - Silveira, Tiago Santos [UNIFESP] (2009)
Introduction: Several factors can reduce the viability of the TRAM flap, among them the nicotine has been made responsible by the loss partial or total of these flaps. Objective: To evaluate the action of the Vascular endothelial Growth Factor in the viability of the Transverse Rectus Abdominis Musculocutaneous, in rats submitted to the nicotine. Methods: Sixty Wistar EPM-1 rats were used, adult males, weighing from 230 to 300g, randomized in 4 groups of 15 animals each: Group Control composed by animals that were submitted to the TRAM flap; Group Nicotine composed by animals that were nicotine exposed and submitted of TRAM flap; Group VEGF composed by animals submitted to the administration of VEGF plasmidial before the TRAM flap; and Group Nicotina+VEGF composed by animals that were exposed to the nicotine, trated with administration of VEGF and submitted to the TRAM flap. For analysis of the results they were done necrosis area and vascular density. Results: There was estatistic significant differentiates in the comparison among all of the groups, regarding the variables necrosis area and vascular density (p <0,05). Conclusion: The Vascular Endothelial Growth Factor increased the viability of the Transverse Rectus Abdominis Musculocutaneous, in rats submitted to the nicotine.